Diseño de una estrategia educativa dirigida al personal de enfermería para sensibilizar sobre la prevención de la violencia obstétrica durante el trabajo de parto y parto en hospitales públicos de Bogotá D.C. (2024)
Obstetric violence is a major problem that impacts numerous women during the pregnancy, labor and delivery process. This form of violence is manifested through humiliation, the performance of unnecessary invasive medical procedures, the lack of information and participation of the pregnant person in decision-making, as well as disrespectful treatment by health personnel towards users